Perbandingan Kinerja Waktu Algoritma ECDSA, EdDSA, RSA, Dan Implementasinya Pada Sistem Multi-Signature Dokumen Pdf - Suantara, Yoga (JATISI, 2024)
In the advancing digital era, digital data security has become a primary concern alongside the increasing cyberattacks and data breaches in line with the growth of information technology. The estimated global losses due to cybercrime, reaching trillions of dollars in 2023, exacerbate this phenomenon. One of the technologies that has been legally recognized in Indonesia since 2008 to safeguard digital data security is digital signatures. In the implementation of digital signatures, several cryptographic algorithms are used, such as ECDSA, EdDSA, and RSA. Although previous research has compared the performance of these three algorithms, attention to their practical applications, especially in the context of multi-signature, remains somewhat limited. Therefore, this research employs an experimental method with a quantitative approach. Within the scope of this study, signatures were applied to documents of varying sizes using the ECDSA, EdDSA, and RSA algorithms. Encryption and decryption time data were analyzed to determine the algorithm with the best performance. The research results show that ECDSA excels in terms of time performance, with an average time of approximately 0.001052 seconds. Hence, ECDSA was chosen for implementation in the multi-signature digital signature system for PDF document